NR2B Antagonist CP-101,606 Abolishes Pitch-Mediated Deviance Detection in Awake Rats - Sivarao, Digavalli V.; Chen, Ping; Yang, Yili; Li, Yu-Wen; Pieschl, Rick; Ahlijanian, Michael K. (Frontiers in Psychiatry, 2014)
Schizophrenia patients exhibit a decreased ability to detect change in their auditory environment as measured by auditory event related potentials such as mismatch negativity. This deficit has been linked to abnormal NMDA neurotransmission since, among other observations, non-selective channel blockers of NMDA reliably diminish deviance detection in human subjects as well as in animal models. Recent molecular and functional evidence link NR2B receptor subtype to aberrant NMDA transmission in schizophrenia. However, it is unknown if NR2B receptors participate in pre-attentive deviance detection. We recorded event related potentials from the vertex of freely behaving rats in response to frequency mismatch protocols. We saw a robust increase in N1 response to deviants compared to standard as well as control stimuli indicating true deviance detection. Moreover, the increased negativity was highly sensitive to deviant probability. Next, we tested the effect of a non-selective NMDA channel blocker (ketamine, 30 mg/kg) and a highly selective NR2B antagonist, CP-101,606 (10 or 30 mg/kg) on deviance detection. Ketamine attenuated deviance mainly by increasing the amplitude of the standard ERP. Amplitude and/or latency of several ERP components were also markedly affected. In contrast, CP-101,606 robustly and dose-dependently inhibited the deviant’s N1 amplitude and as a consequence, completely abolished deviance detection. No other ERPs or components were affected. Thus, we report first evidence that NR2B receptors robustly participate in processes of automatic deviance detection in a rodent model. Lastly, our model demonstrates a path forward to test specific pharmacological hypotheses using translational endpoints relevant to aberrant sensory processing in schizophrenia.